Stapled peptides as a new technology to investigate protein–protein interactions in human platelets. Issue 20 (2nd May 2018) - Iegre, Jessica; Ahmed, Niaz S.; Gaynord, Josephine S.; Wu, Yuteng; Herlihy, Kara M.; Tan, Yaw Sing; Lopes-Pires, Maria E.; Jha, Rupam; Lau, Yu Heng; Sore, Hannah F.; Verma, Chandra; O' Donovan, Daniel H.; et al.
Abstract : We describe the first application of stapled peptides in human platelets. Bim BH3 stapled peptides are used to overcome the limitations of traditional methods and uncover a new role for Bim in platelet activation. Abstract : Platelets are blood cells with numerous crucial pathophysiological roles in hemostasis, cardiovascular thrombotic events and cancer metastasis. Platelet activation requires the engagement of intracellular signalling pathways that involve protein–protein interactions (PPIs). A better understanding of these pathways is therefore crucial for the development of selective anti-platelet drugs. New strategies for studying PPIs in human platelets are required to overcome limitations associated with conventional platelet research methods. For example, small molecule inhibitors can lack selectivity and are often difficult to design and synthesise. Additionally, development of transgenic animal models is costly and time-consuming and conventional recombinant techniques are ineffective due to the lack of a nucleus in platelets. Herein, we describe the generation of a library of novel, functionalised stapled peptides and their first application in the investigation of platelet PPIs. Moreover, the use of platelet-permeable stapled Bim BH3 peptides confirms the part of Bim in phosphatidyl-serine (PS) exposure and reveals a role for the Bim protein in platelet activatory processes. Our work demonstrates that functionalised stapled peptides are a complementary alternative to conventional platelet research methods, and could make a significant contribution to the understanding of platelet signalling pathways and hence to the development of anti-platelet drugs.